2005
DOI: 10.1111/j.1365-2893.2005.00664.x
|View full text |Cite
|
Sign up to set email alerts
|

The current pattern of hepatitis B virus infection in Australia

Abstract: There is little recent data of the seroprevalence of hepatitis B in Australia. We have surveyed a large cohort of endoscopy patients attending a teaching hospital in central Sydney, and related the presence of hepatitis B virus (HBV) markers with putative risk factors for exposure using the SAS statistical package. Of the 2115 patients tested: 2.1% (45/2115) were HBV surface antigen positive, 0.75% (14/2115) viraemic, 9.5% (200/2115) anti-HBs and anti-HBc positive, 20.1% (430/2115) vaccinated (anti-HBs only) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 3 publications
2
36
1
Order By: Relevance
“…In Australia, between 0.5 and 2.0% of the population are chronically infected, and approximately half of these are Asian immigrants (O'Sullivan et al 2004, Tawk et al 2006.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Australia, between 0.5 and 2.0% of the population are chronically infected, and approximately half of these are Asian immigrants (O'Sullivan et al 2004, Tawk et al 2006.…”
Section: Resultsmentioning
confidence: 99%
“…However, no large-scale population-level seroprevalence studies have been undertaken in Australia. Two published opportunistic seroprevalence studies were carried out between 1996(O'Sullivan et al 2004, Tawk et al 2006. In one study, O'Sullivan and colleagues tested for HBV infection in 3,336 stored sera samples that were collected from 45 laboratories around Australia between July 1996and May 1999(O'Sullivan et al 2004.…”
Section: Prevalence Of Chronic Hepatitis B Infectionmentioning
confidence: 99%
“…A national laboratory-based serosurvey has estimated the population prevalence of HBV in Australia to be 0.47-0.87%, while a hospitalbased study found HBsAg seroprevalence of 2.1%. 4,5 A more recent paper based on numbers of people in priority populations and estimates of seroprevalence in these groups, as well as mathematical modelling, estimated overall seroprevalence of 1%. 6 The majority of chronic HBV infections are accounted for by people who were born overseas, especially in the Asia-Pacific region, with estimates from 38% to up to 65%.…”
Section: Seroprevalence Of Chronic Hepatitis B Infectionmentioning
confidence: 99%
“…6,4 In the hospital study of Tawk et al, 70% of those infected were born overseas. 5 Other population groups with higher prevalence include Aboriginal and Torres Strait Islander peoples, people who inject drugs (PWID) and MSM. 6,7 While up to 50% of PWID have markers of HBV infection, the rate of chronic infection is much lower.…”
Section: Seroprevalence Of Chronic Hepatitis B Infectionmentioning
confidence: 99%
“…This study indicates how important it is to identify those individuals who, for whatever reason, have not been tested for hepatitis B. were individuals with HIV, those who were Asian, or those from the Pacific Islands (adjusted odds ratio 36.3-fold and 12.4-fold respectively). 29 Now that we have effective therapies which can prevent both liver disease progression and liver cancer, 1 it is vital that we identify these silent carriers.…”
Section: Other Challenges Facing the Management Of Chronic Hepatitis Bmentioning
confidence: 99%